1996
DOI: 10.1073/pnas.93.21.11859
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of reverse transcriptase in the inhibitory mechanism of CNI-H0294 on HIV-1 nuclear translocation.

Abstract: HIV-1 replication requires the translocation of viral genome into the nucleus of a target cell. We recently reported the synthesis of an arylene bis(methyl ketone) compound (CNI-H0294) that inhibits nuclear targeting of the HIV-1 genome and thus HIV-1 replication in monocyte cultures. Here we demonstrate that CNI-H0294 inhibits nuclear targeting of HIV-1-derived preintegration complexes by inactivating the nuclear localization sequence of the HIV-1 matrix antigen in a reaction that absolutely requires reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…MA and IN bind to importin-␣ as NLS-bearing substrates (Gallay et al 1996(Gallay et al , 1997. It has been suggested recently that HIV-1 Vpr binds importin-␣ at a site distinct from the NLS-binding site (Popov et al 1996), and it was shown that HIV infection of macrophages by Vpr-containing virions is not inhibited by NLS peptide (Gallay et al 1996(Gallay et al , 1997. Therefore, unlike MA and IN, Vpr does not require the importin-␣ NLS-binding site for its transport function.…”
Section: Discussionmentioning
confidence: 99%
“…MA and IN bind to importin-␣ as NLS-bearing substrates (Gallay et al 1996(Gallay et al , 1997. It has been suggested recently that HIV-1 Vpr binds importin-␣ at a site distinct from the NLS-binding site (Popov et al 1996), and it was shown that HIV infection of macrophages by Vpr-containing virions is not inhibited by NLS peptide (Gallay et al 1996(Gallay et al , 1997. Therefore, unlike MA and IN, Vpr does not require the importin-␣ NLS-binding site for its transport function.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear translocation of HIV-1 preintegration complex (PIC) (a nucleic acid/protein complex) is essential for viral replication, because it allows the PIC to get into contact with the cellular chromatin (Haffar et al, 2005). Arylene bis (methylketone) small-molecularweight compounds, such as the agent CNI-H1194, show therapeutic promise by disrupting the formation of the PIC, which could lead to inefficient nuclear import (Dubrovsky et al, 1995;Popov et al, 1996;Gasiorowski and Dean, 2003). However, there is still no consensus about the mechanisms that govern nuclear import of the HIV-1 PIC (Nisole and Saïb, 2004;Haffar et al, 2005).…”
Section: A Viral Therapymentioning
confidence: 99%
“…Alternatively, AH0109 may simultaneously affect both reverse transcription and viral nuclear import. A previous study reported that an anti-HIV-1 compound, CNI-H0294, binds to reverse transcriptase, and this interaction is required for CNI-H0294 to subsequently target the nuclear import signal of the HIV-1 MA protein and inhibit virus nuclear translocation (31). The latter study also suggested that modifications in a CNI-H0294 side chain would allow this compound to inhibit both RT activity and viral PIC nuclear translocation.…”
Section: Discussionmentioning
confidence: 90%